Disrupted Resting-State Functional Connectivity in Hippocampal Subregions After Sleep Deprivation. (1st February 2019) - Zhao, Rui; Zhang, Xinxin; Zhu, Yuanqiang; Fei, Ningbo; Sun, Jinbo; Liu, Peng; Yang, Xuejuan; Qin, Wei
Highlights: Decreased connectivity of the anterior and anterolateral hippocampal subregions was identified after sleep deprivation. The functional connectivity of the middle hippocampal subregion was significantly increased after sleep deprivation. The effect of sleep deprivation on connectivity in different hippocampal subregions was not identical. Abstract: Previous studies have revealed that sleep deprivation (SD) alters hippocampal functional connectivity (FC). However, the effects of SD on the FC of hippocampal subregions are still unknown. In this study, we used a masked independent component analysis (mICA) to partition the hippocampus into several small regions and investigated the changes in the FC of each small region within the whole brain after 24 h of SD in 40 normal young subjects. First, we determined the optimal number of hippocampal subregions in a data-driven manner using a reproducibility analysis and chose 17 as the optimal number of hippocampal subregions. Second, we compared the FC of each subregion between rested wakefulness and SD states using mCIA. Reduced FC was found between the left junction of anterior and anterolateral hippocampal region and the default mode network and bilateral thalamus after SD ( p < 0.05/17, Threshold-Free Cluster Enhancement correction, Bonferroni's corrected for the number of subregions). The FC between the left posterior of the anterolateral and the left lateral posterior of the anterior hippocampal regions and somatomotor network changed more negative after SD. However, increased FC was identified between the left middle hippocampal region and vision-related regions after SD. Our results reflect differential effects of SD on the FC in specific hippocampal regions and provide new insights into the impact of SD on the resting-state functional organization in the human brain.